Contradictory time horizons of Durban energy piping in an era of looming climate chaos. Issue 4 (3rd September 2019) - Bond, Patrick
Abstract : The contradictory role of time in urban capital's uneven development can be observed through the analytical lens of infrastructure investment. The two cases considered below are energy pipelines in Durban, South Africa. On the one hand, urgency is associated with greenhouse-gas emissions mitigation, to slow climate change that is already doing enormous damage in this city. Yet on the other hand, the lengthy payback of mega-project investments made in long-term fossil fuel projects (and hence their reliance upon public subsidisation and guarantees) and the financial difficulty of switching to low-carbon transport, energy and waste disposal systems, together mean that temporal contradictions loom large. In sum, it appears impossible to align socio-ecological survival needs with investors' profit-driven time horizons. This is the case involving a controversial pipeline for petroleum products from the African continent's largest refinery complex (South Durban) to its largest market (Johannesburg), constructed at the same time as was piping to redirect methane that is emitted from the continent's largest landfill, into a new electricity generator (in central Durban). The context, globally and locally, is that the 'displacements' of overaccumulated capital into infrastructure finance (and then specifically into piping systems) hit both temporal and spatial barriers, failing to deliver the promised returns on the infrastructure investments. With such insights, critical urban activists can better apply contrary analysis—of time, space, scale, class, race and environmental overlaps—whenever local growth coalitions parrot the slogan used to justify massive public subsidization of this infrastructure on behalf of investors: 'build it, and they will come.' The next question: who wins and loses —and when?